The Assimilation model, modern human origins in Europe, and the extinction of Neandertals - Smith, Fred (Array, 2005)
Debate continues concerning the role of the Neandertals in the emergence of early modern Europeans. This paper presents one assessment of aspects of the morphological data, chronological patterns, genetic information and archaeology relevant to the debate. It is clear that none of these unequivocally support any of the models offered to explain modern human origins. In fact despite various claims to the contrary, there continues to be valid scientific debate about the interpretation of patterns from all of these disciplinary domains and which models they are more commensurate with. The assessment presented here concludes that the Assimilation Model is the best explanation for the origin of anatomically modern humans in Europe. If Neandertals are assimilated into in-migrating populations of modern people in Europe, then Neandertals do not go extinct in the classical sense of the word.